The Influence Of Facilities And Service Quality On Visitor Satisfaction At Sari Ater Hot Spring As A Wellness Tourism Destination - Zalfa Khairunnisa; Irena Novarlia; Oman Sukirman (UNIVERSITAS PAKUAN, 2026)
This study aims to analyze the effect of facilities and service quality on visitor satisfaction at Sari Ater Hot Spring as a wellness tourism destination. A quantitative approach with a survey design was employed, using questionnaires distributed to visitors. The data were analyzed through descriptive statistics, classical assumption tests, and multiple linear regression. The results show that both facilities and service quality have positive and significant effects on visitor satisfaction, both partially and simultaneously. Facilities, including condition, completeness, and design, contribute to visitor comfort, while service quality, reflected in responsiveness, reliability, and courtesy, enhances visitor experience. The coefficient of determination indicates that these variables explain a substantial proportion of satisfaction, although other factors also play a role. Overall, improving facilities and service quality is essential for increasing visitor satisfaction and maintaining competitiveness in the tourism industry, particularly in wellness tourism destinations.